Intracellular adaptation of Brucella abortus - Lamontagne, Julie (2009)
Macrophages were infected with virulent B. abortus strain 2308 or attenuated strain 19. Intracellular bacteria were recovered at different times after infection and their proteomes compared. The virulent strain initially reduced most biosynthesis and altered its respiration, adaptations reversed later in infection. The attenuated strain was unable to match the magnitude of the virulent strain’s adjustments. The results provide insight into mechanisms utilized by Brucella to establish intracellular infections